(untitled) (ModaPalavra e-periódico, 2018)
This is an interview with Professor Edna Maria dos Santos Silva, who developed and implemented, from your Master’s research, an Open Educational Resource as a tool to support the teaching-learning process of discipline Flat Modeling. The interviewee talks about the resource created and the repercussion of this among the students, as well as other aspects of to the experience as a teacher of the Technician in Clothing and Technological Superior in Fashion Design courses.